2011
DOI: 10.1159/000327373
|View full text |Cite
|
Sign up to set email alerts
|

Short Children with Low Birth Weight Born either Small for Gestational Age or Average for Gestational Age Show Similar Growth Response and Changes in Insulin-Like Growth Factor-1 to Growth Hormone Treatment during the First Prepubertal Year

Abstract: Background/Aims: Growth hormone (GH) is an accepted treatment for short children born small for gestational age (SGA). The aim of this analysis was to compare the growth response to GH in children with low birth weight born SGA or appropriate for gestational age (AGA). Methods: This retrospective observational study is from one center. Of all the children with a birth weight <2,500 g treated, 50 were primarily diagnosed as having growth hormone deficiency ([A] SGA, n = 26; [B] AGA, n = 24) and 138 were origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
4
3
0
1
Order By: Relevance
“…The indicators of GH sensitivity IGF-1 and IGFBP-3 were measured throughout this study; they were low at the start of treatment and showed a similar increase in both groups (table 3), as expected from our previous studies [21]. …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The indicators of GH sensitivity IGF-1 and IGFBP-3 were measured throughout this study; they were low at the start of treatment and showed a similar increase in both groups (table 3), as expected from our previous studies [21]. …”
Section: Discussionsupporting
confidence: 85%
“…Our data show no significant differences between AGA and SGA children in their auxological parameters at the start of GH treatment. This has already been described in recent studies [1,2,3,6,21]. …”
Section: Discussionsupporting
confidence: 73%
“…The availability of recombinant human growth hormone (hGH) (rhGH) in the past 30 years has led to its use in nongrowth hormone deficient conditions (29) such as Turner Syndrome (30 -32), small for gestational age (SGA) (33,34), idiopathic short stature (35), short stature homeobox (SHOX) deficiency (36), Prader Willi Syn-drome (37) and chronic renal insufficiency (38). In younger prepubertal children with chronic disease and in those with pubertal delay who continue to grow slowly despite pubertal induction, rhGH may be a therapeutic option.…”
Section: Age Of Presentation Of Chronic Disease In Childhoodmentioning
confidence: 99%
“…Further, current definitions of ISS exclude children who were born small for gestational age, although it is a separate indication for GH treatment in many countries2. There is conflicting evidence for whether children who are small for gestational age respond similarly to children who were appropriate for gestational age at birth1718. The New Zealand GH treatment programme was started well before this consensus, and so birth weight were not part of the entry criteria for ISS in New Zealand and so are not available for most children.…”
Section: Discussionmentioning
confidence: 99%